2014
DOI: 10.1016/j.neurobiolaging.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Migration of neutrophils targeting amyloid plaques in Alzheimer's disease mouse model

Abstract: Immune responses in the brain are thought to play a role in disorders of the central nervous system, but an understanding of the process underlying how immune cells get into the brain and their fate there remains unclear. In this study, we used a 2-photon microscopy to reveal that neutrophils infiltrate brain and migrate toward amyloid plaques in a mouse model of Alzheimer’s disease. These findings suggest a new molecular process underlying the pathophysiology of Alzheimer’s disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 18 publications
8
126
0
3
Order By: Relevance
“…SERPINB1 is expressed in the human brain, primarily in microglia and macrophages [84]. Recent research of transgenic mouse models for AD (5×FAD and 3×Tg-AD) reported that neutrophils were present in the brain near Aβ deposits, and researchers observed neutrophil migration from blood into the brain toward amyloid plaques [4, 83]. They discovered that Aβ 42 triggered the high-affinity state of integrin LFA-1, which is necessary for neutrophil infiltration of the CNS [83].…”
Section: Discussionmentioning
confidence: 99%
“…SERPINB1 is expressed in the human brain, primarily in microglia and macrophages [84]. Recent research of transgenic mouse models for AD (5×FAD and 3×Tg-AD) reported that neutrophils were present in the brain near Aβ deposits, and researchers observed neutrophil migration from blood into the brain toward amyloid plaques [4, 83]. They discovered that Aβ 42 triggered the high-affinity state of integrin LFA-1, which is necessary for neutrophil infiltration of the CNS [83].…”
Section: Discussionmentioning
confidence: 99%
“…75 A role for neutrophils in these conditions is largely based on 2 observations: 1) neutrophils are recruited into the diseased/injured tissue, and 2) interfering with the neutrophil accumulation minimizes or prevents the endothelial barrier dysfunction. 76,77 Activated neutrophils release an impressive mixture of chemicals that can impair endothelial barrier function, including reactive oxygen species (ROS), proteolytic enzymes, and cytokines ( Fig.…”
Section: Leukocytes and Endothelial Barrier Functionmentioning
confidence: 99%
“…Peptides were prepared as the literatures [23][24][25][26]. Briefly, the powdered Aβ was first dissolved in 4 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) to a concentration of 1mg/mL.…”
Section: Materials and Reagentsmentioning
confidence: 99%